EVALUATION OF THE REHABILITATION PROGRAM FOR UNINHABITABLE HOUSES IN CIJULANG VILLAGE PANGANDARAN DISTRICT - Fatimah Nurul Azizah; Abdul Mutholib; Budi Setiadi (Faculty of Social and Political Science Universitas Galuh, 2023)
The purpose of this research was to evaluate of rehabilitation program for uninhabitable houses (RUTILAHU) in Cijulang village, Pangandaran district with the problems is limited provision of livable housing, an increase in the number of households occupying houses that are unfit for habitation, and not supported by adequate environmental facilities and infrastructure, and also the increasingly widespread slum settlements. Therefore, this research focuses on the Evaluation of Uninhabitable House Rehabilitation Program in Cijulang Village, which, in 2020 Cijulang Village received 3 (three) repaired housing units and is a Low-Income Community (MBR). This research used the descriptive qualitative method and also the data and data sources using primary and secondary data. The data aggregation techniques are interviews, observation, and documentation Additionally, data analysis techniques used are data reduction, presentation of data, conclusion, and verification. The results of this research showed that the Uninhabitable House Rehabilitation Program was helpful once and very effective in eradicating uninhabitable houses, especially for low-income people (MBR). This research states that the evaluation of rehabilitation programs for uninhabitable houses in Cijulang Village, Pangandaran Regency becomes important attention for stakeholders in handling the problems of uninhabitable houses and can provide recommendations for the improvement in the future.